Framework for enhancing students’ smartphone learning ability: a case study of Nigerian public Universities - Esechie, Godswill Ejeohiolei; Ohueri, Chukwuka Christian; Siti Zanariah, Ahmad Ishak; Nwanesi, Peter Karubi (2021)
Purpose The importance of smartphones in enhancing students learning, research and development is well-established in many published studies. Nevertheless, due to numerous challenges, Nigerian students are yet to reap from the benefits of smartphones in terms of accessing vital information for learning and development. Therefore, this study aims to develop a framework that will enhance Nigerian students’ ability to use smartphones for learning.